A utilização de experimentos de baixo custo em sala de aula: uma revisão da bibliografia no ensino de física. - MACHADO, Thiago Almeida (2024)
Physics education over the last decades has been adapting to new trends, motivated by great technological development, which affects several areas. For example, in the field of research in Physics Teaching, we noticed some tendencies to insert new methodologies aimed at the use of more sophisticated and technological practices in Basic Education. In this context, we realize that there are some problems regarding the use of these practices, by the teachers, in Physics Education. We can mention a series of issues that contribute to this situation, such as the lack of accessibility, lack of career motivation, lack of public policies, and deficits in training. Thus, the Low-Cost Experiment (LCE) appears as a viable alternative on the condition of making Physics more attractive to students, in different contexts, such as remote educational practices, currently caused by the Pandemic of the new Corona Virus (SARS - CoV2). Thereby, the present work proposes a Bibliographic Review of two National Journals (Brazilian Journal of Physics Teaching and Brazilian Physics Teaching Notebook), to answer some guiding questions about the relationship between research in Physics Education and the use of CBE in the classroom. The present research tries to understand if there is an interest of the Brazilian scientific community, in these experimental approaches, their characterizations, relevance, and perspectives for the Teaching of Physics.